A Case of Large Extraovarian Endometriotic Cyst in Pelvis Mimicking Ovarian Cancer - Çayan, Filiz; Dilek, Umut; Cinel, Leyla; Yazıcı, Gürkan; Dilek, Saffet (Gynecology Obstetrics & Reproductive Medicine, 2006)
Endometriosis is defined as an ectopic implantation of uterine mucosal tissue outside the uterine cavity, usually in the pelvis. The areas of the pelvis most frequently affected are the peritoneum, the ovaries, the poch of douglas and the uterosacral ligaments. In this paper, we report an extremely rare case with an extraov arian large endometriotic cyst originated from the peritoneum overlying the bladder. Endometriotic cyst should be kept in mind as a possible diagnosis in the presence of an extraovarian pelvic mass.